Survey on the State of Digital Human Rights Management and Internet Use in Uganda - Mirembe, Drake Patrick; Lubega, Jude; Kibukamusoke, Martha; Nambogo, Fiona (Archives of Business Research, 2022)
There is tremendous increase in the use of Internet across the world including Uganda. Freedom of internet use including documentation of rights violation has been done in Uganda, defending the rights of victims has been low because the existing legal framework and new policies limiting internet access, free speech have further suffocated them. The paper presents results from a study conducted using mixed methods approach on the digital human rights in Uganda. Data collection (qualitative and quantitative) techniques applied and followed by a rigorous systematic scientific inquiry along the processes of; facts determination, analysis and reporting. The aim of the study was to explore the uncertainties in the policies that limit the use of internet and digital human rights enjoyment. Of the 525 target respondents, 547 participated in the study with; 451 citizens, 17 media, 41 state actors, 17 special interest groups, 9 women rights activists and 12 others. Furthermore, the results showed that the factors hindering the enjoyment of digital rights and internet freedoms include government failure to monitor set policies, failure to sensitize people on digital rights, limited knowledge on existence of digital rights, high charges on using social media and gender inequality.